First reported case of late recurrence of pulmonary mucormycosis in a renal transplant recipient with poorly controlled diabetes mellitus. Issue 12 (10th November 2021) - Leung, Cheuk Cheung Derek; Chan, Yu Hong; Ho, Man Ying; Chan, Ming Chiu; Chen, Chun Hoi; Kwok, Chin Tong; Yeung, Yiu Cheong
Abstract: Pulmonary mucormycosis (PM) is a rare, life‐threatening fungal infection usually affecting immunocompromised patients. Its incidence is rising, with a recent outbreak associated with COVID‐19 co‐infection. Amphotericin B along with early surgery are considered the standard treatment. Recurrence has been reported in patients without adequate treatment and without permanent reversal of predisposing factors. We report a case of late recurrence of PM in a renal transplant recipient. In 2012, he was diagnosed with PM. Imaging at the time showed a lingular mass. He was treated with antifungal for 1 year until complete radiological resolution. Surgical intervention was considered but no further follow‐up action was taken. In 2020, he presented with fever and haemoptysis. Imaging again showed a lingular mass, which was confirmed to be PM by bronchoscopic lung biopsy. This case highlights the importance of secondary antifungal prophylaxis for PM if permanent reversal of immunosuppression is not possible. Abstract : We report the first case of late recurrence of pulmonary mucormycosis (PM) and highlight the importance of secondary antifungal prophylaxis for PM if permanent reversal of immunosuppression is not possible.